Characterization of Jordan Vectors of Operator-Valued Functions with Applications in Differential Equations - Borogovac, Muhamed (Sarajevo Journal of Mathematics, 2026)
A well-known characterization of Jordan vectors of a matrix polynomial $L(z)$ is generalized to a characterization of Jordan vectors of the operator-valued function $Q(z)$ at an eigenvalue $α \in \mathbb{C}$. The results are then applied to solve a system of nonlinear ordinary differential equations.